SCYLLA AND C HARYBDIS OF EDUCATION: SPECULATIONS ON THE PROBLEMS OF THE ENGLISH LANGUAGE TEACHING IN HIGHER SCHOOLS OF RUSSIA - Natalya K. Ivanova; Marina N. Mileeva (Высшее образование в России, 2016)
The paper considers some actual problems of the foreign languages teaching in the context of the new challenges faced by Russian higher school and demands for building its competitive scientific and educational image and for increasing international scientific ranking. The complex of the problems relating to Englishization – the application of the English language in national educational and research processes – is discussed, internal and external factors of ineffective traditional methods of teaching in Russian higher schools are revealed, comparison with European approaches to foreign language teaching is made. On the basis of the theoretical sources and practical experience of EFL teaching a number of efficient techniques and necessary measures for overcoming “language backwardness” of Russia are described.